Feeding Habit and Lifestyle Influence the Baseline Micronuclei Frequency of Crab Species in Pristine Mangroves - Pinheiro, Marcelo Antonio Amaro [UNESP]; Kriegler, Nicholas [UNESP]; de Souza, Caroline Araújo [UNESP]; de Almeida Duarte, Luis Felipe [UNESP] (Springer Nature, 2021)
Metals are harmful inorganic pollutants in aquatic environments when their concentrations are higher than expected (or tolerated) and, in low concentrations, they can lead sublethal genetic injuries. Baseline frequencies of micronucleated cells (MN‰) of three mangrove crab species were established in a pristine mangrove (Juréia-Itatins Ecological Station, JIES). Aratus pisonii, Ucides cordatus and Goniopsis cruentata belong to different functional groups, regarding the diet and lifestyle. Overall, the baseline MN‰ of G. cruentata (1.7 ± 1.2; mean ± sd) was higher than that of A. pisonii (0.9 ± 1.1) and U. cordatus (1.3 ± 0.9). These differences can be explained by the diet (gl, green leaves; sl, senescent leaves; a, animal items; or their combination) and lifestyle of these species, as their degree of contact with abiotic compartments (w, water; s, sediment). Aratus pisonii is an arboreal crab and specialist herbivore, associated with few compartments (w + gl); Ucides cordatus is a digger crab, generalist herbivore, using three compartments (w + s + sl); and Goniopsis cruentata is a cursorial crab, omnivorous, exploring more compartments (w + s + sl + a). Thus, using a broader range of compartments and a more diverse diet were correlated with a higher genotoxicity. Metals in JIES were registered in environmentally safe concentrations but seem to influence the baseline MN‰ in crab species. Higher genotoxicity was registered in species that interact with more compartments (especially the sediment), a fact that should be considered in monitoring processes.
Keywords: Conservation; Crustacean; Estuary; Genotoxicity; Metal; Monitoring